PROSUMER AND DIGITAL LABOR ON FOOD VLOGGER AS WORD OF MOUTH POWER IN THE DIGITAL ERA - Bagya Sugihartana; Udi Rusadi (International Journal of Social Science, 2024)
This research is based on the emergence of a new profession due to the development of digital technology, namely food vlogger. This digital work sector is a form of application of the prosumer concept which is of great interest to the public, especially in Indonesia. The aim of this research is to analyze the prosumer concept in food vloggers which can become the power of word of mouth marketing communications in the digital era. The research method used is a qualitative literature study method. The data source uses secondary data from a number of related literature such as books, journals and scientific research, news articles and documents. Based on the results and previous discussions, this research concludes that the prosumer concept in food vloggers has been able to become a force for word of mouth marketing communications in the digital era because of several aspects, namely food vloggers with many followers have a stronger message and appeal in influencing people's behavior. Food vloggers carry out two important functions in mass communication and marketing communication practices, namely as gatekeepers and as new media in e-Word of Mouth strategies in digital communication contexts. The role of food vloggers in the successful marketing of a product is very important. And food vloggers are influential in the context of digital capitalism because of their ability to eliminate time constraints in the process of producing and consuming messages and content